Household poverty effects and youth’s life aspiration in Kwara state, Nigeria (2024)
The poverty experienced by youth is commonly linked to childhood deprivation and parental poverty which have implications across an individual’s life-course including life aspiration. This study therefore investigated the effects of household poverty on life aspiration of youth in Kwara state. Systematic sampling technique was used to select 180 respondents for the study. Data was collected through structured questionnaire and analyzed using frequency counts, percentages mean Chi-square, Pearson Product Moment Correlation (PPMC), and T-test. Results revealed that 50.0% of respondents were male and female, with mean age of 22.2±3.5. and mean household size of 7± 2.6 people, while the primary occupation of most of the respondents’ parents was trading (27.2%). Prayer (x=1.08), ranked first as the coping strategies against poverty. Household poverty was high (51.1.4%) likewise life aspiration (54.4%). Aspiration categories such as personal growth (x=14.07), wealth (x=13.0) community contribution (x= 10.8) were the most important life aspirations of the respondents. Parents’ Primary occupation (/2= 25.415, p=0.000), Age (i=-0.153, p=0.041) and household poverty (r=0.338, p=0.000) had significant relationship with level of aspiration. There was also a significant difference in life aspiration of urban and rural youth (t= 3.218, p=0.003). The study concluded that household poverty had significant effect on life aspiration of youth. Governmental interventions should encourage a mentorship programme that will target young people from poor households.